Differential deregulation of NGF and BDNF neurotrophins in a transgenic rat model of Alzheimer's disease - M. Florencia Iulita; M. Beatriz Bistué Millón; Rowan Pentz; Lisi Flores Aguilar; Sonia Do Carmo; Simon Allard; Bernadeta Michalski; Edward N. Wilson; Adriana Ducatenzeiler; Martin A. Bruno; Margaret Fahnestock; A. Claudio Cuello (Neurobiology of Disease, 2017)
Evidence from human neuropathological studies indicates that the levels of the neurotrophins nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) are compromised in Alzheimer's disease. However, the causes and temporal (pathology-dependent) evolution of these alterations are not completely understood. To elucidate these issues, we investigated the McGill-R-Thy1-APP transgenic rat, which exhibits progressive intracellular and extracellular amyloid-beta (Aβ) pathology and ensuing cognitive deficits. Neurochemical analyses revealed a differential dysregulation of NGF and BDNF transcripts and protein expression. While BDNF mRNA levels were significantly reduced at very early stages of amyloid pathology, before plaques appeared, there were no changes in NGF mRNA expression even at advanced stages. Paradoxically, the protein levels of the NGF precursor were increased. These changes in neurotrophin expression are identical to those seen during the progression of Alzheimer's disease. At advanced pathological stages, deficits in the protease cascade controlling the maturation and degradation of NGF were evident in McGill transgenic rats, in line with the paradoxical upregulation of proNGF, as seen in Alzheimer's disease, in the absence of changes in NGF mRNA. The compromise in NGF metabolism and BDNF levels was accompanied by downregulation of cortical cholinergic synapses; strengthening the evidence that neurotrophin dysregulation affects cholinergic synapses and synaptic plasticity. Our findings suggest a differential temporal deregulation of NGF and BDNF neurotrophins, whereby deficits in BDNF mRNA appear at early stages of intraneuronal Aβ pathology, before alterations in NGF metabolism and cholinergic synapse loss manifest.